1996
DOI: 10.1063/1.470830
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-mechanical study of the I2–Ne vibrational predissociation dynamics: A three-dimensional time-dependent self-consistent-field approach

Abstract: Articles you may be interested inA full-dimensional quantum approach to the vibrational predissociation of tetra-atomic complexes based on the partially-separable time-dependent self-consistent-field approximation J. Chem. Phys. 116, 6595 (2002) A three-dimensional time-dependent self-consistent-field ͑TDSCF͒ approach is proposed to study the vibrational predissociation of the I 2 (B) -Ne van der Waals ͑vdW͒ complex. Jacobian coordinates are used within the assumption of zero-total angular momentum. In the met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
1

Year Published

1996
1996
2004
2004

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 72 publications
0
14
1
Order By: Relevance
“…It is found that the rotational state distributions of product I 2 through ∆v = −1 channel are notably different from those through ∆v = −2 channel. 14,24 But, here we do not present analyses on the distributions through higher channels because the ∆v = −2 or up channels do not contribute much to the total predissociation rate. The predissociation rates for ∆v = −2 are one or two orders of magnitude smaller than the ∆v = −1, and the ∆v = −3 rates are even smaller than the ∆v = −2.…”
Section: Computations and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is found that the rotational state distributions of product I 2 through ∆v = −1 channel are notably different from those through ∆v = −2 channel. 14,24 But, here we do not present analyses on the distributions through higher channels because the ∆v = −2 or up channels do not contribute much to the total predissociation rate. The predissociation rates for ∆v = −2 are one or two orders of magnitude smaller than the ∆v = −1, and the ∆v = −3 rates are even smaller than the ∆v = −2.…”
Section: Computations and Resultsmentioning
confidence: 99%
“…Since the early stage of predissociation research, [3][4][5][6] the vibrational predissociation of I2(B)-Ne(in the excited 3 Π (0u + ) electronic state 7 ) has been most frequently investigated. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] The first investigation by Levy's group measured predissociation rates and some excited vibrational energy levels of I2(B)-Ne. [3][4][5][6] The accurate vibrational predissociation rates (or lifetimes) of I2(B)-Ne(v1, 0, 0) were first reported by Zewail and coworkers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…46 In the case of I 2 -Ne n clusters with nϾ1, the diatomic cromophore is coupled to dissociating modes and also to a number of nondissociating ''bath modes'' which increases with n, and may play an important role in the dynamics. In fact, the mechanism of cluster dissociation can be affected by these bath modes, potential acceptors of the I 2 vibrational energy.…”
mentioning
confidence: 99%
“…[29][30][31][32] The appearance of time-domain experimental data, along with the development of techniques to solve efficiently the time-dependent Schödinger equation [33][34][35][36] gave a great impulse to the use of timedependent approaches. Exact [37][38][39][40] and approximate [41][42][43][44][45][46][47] time-dependent methods have been applied to van der Waals clusters, most of them triatomic and tetraatomic systems. In a series of papers 5 Zewail and co-workers have reported real-time experiments on the vibrational predissociation ͑VP͒ of the I 2 -Ne n ͑nϭ1-4͒ clusters.…”
mentioning
confidence: 99%